Modern family. The eleventh and final season [videorecording (DVD)]. - O'Neill, Ed, 1946-; Bowen, Julie; Burrell, Ty, 1967-; Vergara, Sofía, 1972- (20th Century Fox Television, 2020)
The misadventures of the Pritchett-Dunphy-Tucker clan are as hilarious as ever in the celebrated comedy serie's final season. When Phil and Claire babysit the twins, Haley and Dylan realize they're the more responsible parents. While Manny's still rebounding from heartache, Phil's still trying to bond with Jay. And although they're raising Lily with a positive self-image, Mitch and Cam discover their own insecurities. Through it all, the love and laughter live on.